Compatibilidade de pimenteira-do-reino enxertada em espécies do gênero Piper - Crasque, Jeane (2020)
In the black pepper culture, Brazilian productivity is restricted by several biotic and abiotic factors, highlighting the incidence of the fungus Fusarium solani f. sp. Piperis, since the existing chemical management techniques are not very efficient. Among the strategies, the practice of grafting black pepper cultivars into wild species has proved to be efficient and sustainable, however, the success of this technique depends on the compatibility between the graft and rootstock. Thus, the objective of this study was to evaluate the efficiency of grafting using various rootstocks and to identify morphophysiological descriptors related to incompatibility. Fusarium species resistant to Piper species were studied using two grafting techniques. In the lateral fork, three native species of the genus Piper (Piper aduncum L., Piper hispidum Sw. And Piper tuberculatum Jacq.) And the cultivar BRS Kottanadan were evaluated as rootstocks. In the top fork experiment, three native species of the genus Piper (Piper arboreum Aubl., P. aduncum and P. tuberculatum) and ´Bankankotta` were evaluated as rootstocks, and as a graft from both trials, cultivar was used Bragantina. The first chapter was entitled “Chlorophyll a fluorescence for assessing the efficiency of grafting of black pepper (Piper nigrum L.) under intra and interspecific rootstocks” and the second, entitled “Primary metabolism and its relationship with development of grafted seedlings of black pepper ”. When the photosynthetic apparatus was analyzed using the chlorophyll a fluorescence method, grafting under wild species was better in both grafting methods with a higher performance index of photosynthetic efficiency. The recommended method, at the production level, is the grafting of the side fork in a full slit. It can be concluded that grafting is a viable strategy for mitigating biotic and abiotic factors. As for chapter two, characteristics related to vegetative development, gas exchange, photosynthetic pigments, carbohydrate allocation were evaluated. P. tuberculatum showed initial incompatibility. The analysis of survival over time and the parameters related to the photosynthetic capacity of the graft and seedling quality indicated that there was no incompatibility between ´Bragantina` and the rootstocks P. aduncum, P. hispidum vii and ´Kottanadan`. However, the species P. hispidum and ´Kottanadan` showed greater limitation in union due to difference in diameter. In the study of correlations, it was possible to observe a decrease in investment in aerial parts, contributing to the increase in water use efficiency. The content of AR and AST of the stem above the graft region allowed greater accumulation of dry mass in this region. The species with the highest photosynthetic performance and carbohydrate allocation was P. aduncum